Digitally mediated martyrdom: The role of the visual in political Arab activist culture. (1st November 2019) - Lewis, Kelly
Digitally mediated images depicting death and martyrdom as a trope of resistance and contestation against oppressive regimes emerged as recurring and critical instruments of dissent during the Arab uprisings of 2010‐11. While the trope of death and martyrdom as a form of political expression and resistance is not a new phenomenon in the Middle East, the affordances of digital and social media technologies have brought forth new opportunities for activists and everyday citizens to construct, circulate and communicate martyr narratives. Drawing from literature in visual politics, digital activist culture, and media and communication, this textual and iconographical analysis of visual tropes focuses on the brutal killing of Egyptian youth Khaled Said, on his construction as a posthumous injustice symbol, and on his subsequent transformation as a martyr of the 2011 Egyptian Revolution. Activists and everyday citizens participated in symbolically resurrecting Said in and through digitally mediated images and transforming him into a martyr to represent the popular struggle for social justice and universal human rights. The article examines how Said is made a martyr through complex creative processes of recurrent visual appropriation, mediation, re-appropriation and remediation. It shows that the creative authorship of martyrdom is increasingly hybridized, decentralized and driven by a memetic protest dynamic. The article proposes the term 'digitally mediated martyrdom' to designate the emergence of a new kind of visually oriented, socially constructed and ritualized protest dynamic. It develops the conceptual framework for understanding digitally mediated martyrdom as a contemporary political practice within activist cultures and popular social justice movements. It also argues digitally mediated martyrdom represents the emergence of a new and transnational protest dynamic.